(untitled) (Texas Journal of Medical Science, 2026)
Surgical treatment of thyroid diseases remains one of the main therapeutic approaches, while the choice of surgical extent (total or subtotal thyroidectomy) influences postoperative outcomes and patients’ quality of life. The aim of this study was to perform a comparative analysis of quality of life indicators following total and subtotal thyroidectomy. A prospective study involving 140 patients was conducted. Quality of life was assessed using the ThyPRO questionnaire. No statistically significant differences in the overall quality of life between the groups were identified (p>0.05); however, symptoms of hypothyroidism were more frequently observed after total thyroidectomy, whereas anxiety related to the risk of recurrence was more common after subtotal thyroidectomy. The incidence of hypoparathyroidism reached up to 22%, and transient recurrent laryngeal nerve paresis was observed in approximately 6.5% of cases. The obtained data confirm the comparability of these surgical methods despite differences in certain clinical aspects.